Teenage Pregnancy and Low Birth Weight Babies at Patan Hospital - Shrestha, Sitaram (Journal of General Practice and Emergency Medicine of Nepal, 2014)
Introduction: Teenage pregnancy is related to increased maternal and new born mortality and morbidity. Increase delivery of low birth weight is one of the important adverse outcome of teenage pregnancy.1 This study is done to evaluate the prevalence of low birth weight in teenage pregnancy. Methods: This is a cross section study conducted at Patan hospital. Data from the delivery record from August 2010 to July 2011. Incidence of teenage pregnancy along with low birth weight were recorded. Results: Out of 8587 deliveries during one year period, teenage pregnancy was 4.4%. Out of 375 teenage pregnancies 24% deliveries resulted in low birth weight baby. Conclusion: Teenage pregnancy was observed in this study also along with deliveries resulting in low birth weight.